COVID-19 Cluster among 2020 Matric Rage Festival Attendees, KwaZulu-Natal Province, South Africa, November–December 2020. (March 2022) - Shonhiwa, A.M.; Tshabane, C.; Born, K.; Ngoma, N.; Pillay, S.; Thabane, E.; Matiea, I.; Mdose, H.; Nevashan, G.; Ntshoe, G.; Vivien, E.
Abstract : Purpose: South Africa moved to lockdown alert Level-1 on 20 September 2020 midnight, lockdown regulations were relaxed, gatherings were permitted with the number of people not exceeding 50% of normal venue capacity. The National Institute for Communicable Diseases was alerted by a clinician of a number of COVID-19 cases amongst young people who reportedly have attended the 2020 Matric Rage Festival, KwaZulu-Natal Province. This prompted an investigation to ascertain the existence of a COVID-19 cluster related to attendance of Rage Festival (Rage) and provide epidemiological characteristics of the cluster. Methods & Materials: We conducted a retrospective cohort investigation amongst 2 253 attendees. A cluster was defined as the identification/presence of ≥two laboratory confirmed COVID-19 cases amongst individuals who attended the Rage between 27 November to 4 December 2020. COVID-19 confirmed cases were identified using the organizers ticket purchaser and crew record list and the national COVID-19 laboratory confirmed cases line-list. A standardized questionnaire was circulated to 1814 attendees using Google Forms. A case was defined as any person within the cohort with SARS-CoV-2 RT-PCR positive results. Results: Of the 2 253 attendees, 848 (37.6%) cases were identified, of which 846 (99.8%) were revelers and two were crew members (0.2%). Age ranged from 16 to 58 years (Median: 18, IQR: 18-18). The 15-19-year-old age group accounted for 802 (94.6%) of the cases, while 53.0% (425/802) were males. Most cases were from Gauteng (66.2%, 561/848), followed by KwaZulu-Natal (30.0%, 254/848). Two of the attendees had positive SARS-CoV-2 results approximately 7-10 days before the festival. The questionnaire response rate was 1.0% (19/1814). Revelers attended other large events and private parties and mask wearing and social distancing was not always practiced. Conclusion: Although organizers observed COVID-19 precautions and protocols; social distancing and mask wearing were compromised. Factors such as mass gathering without using appropriate personal protective equipment, crowded spaces, poor hygiene and ventilation may have produced a conducive environment for SARS-CoV-2 transmission. The study limitations included delayed questionnaire circulation, lack of contact tracing data to determine secondary attack rate, and lack of clinical information amongst cases. Non-pharmaceutical interventions are effective recommended prevention and control measures.